Self‐assessed impact of oral health on the psychological well‐being and depressive symptoms of older adults living in Melbourne. (13th April 2020) - Mariño, Rodrigo; Enticott, Joanne; Browning, Colette; Elsamman, Mahmoud; Etzion, Rachel; Ferooz, Maryam; Fujihara, Ryuun; Hancock, Hugo; He, Julian; Kendig, Hal
Abstract: Objectives: This study aimed to investigate oral health‐related factors affecting the self‐assessed psychological well‐being (PW) and depressive symptoms of independent‐living Australians aged 79 years and over living in the community in metropolitan Melbourne. Methods: The Melbourne Longitudinal Studies on Healthy Aging (MELSHA) program was used as the data source in this study and includes data on the health and well‐being of older participants. The MELSHA baseline data collection occurred in 1994, the current study used data from the 2008 data collection and included 201 participants, who remained in the study. Data were analyzed using multiple linear regression (MLR) analysis with a stepwise procedure to identify the variables that accounted for a significant proportion of the variance in the participants' PW scores. Results: Present findings indicate that oral health may play a significant mediating role in PW through maintaining a presentable and acceptable physical appearance. Some 16.4 percent of participants reported feeling concerned about their dental appearance, either "Sometimes, " "Often, " or "Very often." Multivariate analysis showed significantly influences on PW positive and negative affect scores ( P < 0.0001); and depressive symptoms ( P < 0.0001) by participants' dentition status, enjoyment of meals, self‐reported feeling of concern about the appearance of the mouth, social activity and self‐assessment of general health. Final models explained 17.8, 20.1, and 24.6 percent of the variance of PW positive, negative affect scores, and depressive symptoms, respectively. Conclusions: Oral health, specifically the appearance of the mouth and dentition, plays a significant role in the PW of older Melbournians. Future cross‐sectional and longitudinal studies are indicated to raise awareness on the changes required to improve the quality of life of the older population.